Fundamentals of geotechnical engineering - Das, Braja M.
This book combines the essential components of Braja Das' market leading texts, PRINCIPLES OF GEOTECHNICAL ENGINEERING and PRINCIPLES OF FOUNDATION ENGINEERING. It includes the fundamental concepts of soil mechanics as well as foundation engineering, including bearing capacity and settlement of shallow foundations (spread footings and mats), retaining walls, raced cuts, piles, and drilled shafts